Evaluation of the Impact of the Smart Indonesia Program (PIP) on Underprivileged Families in Improving Access and Sustainability of Education - Nurlita Zein; Erlina Trianingrum; Tria Fajriana; Setyana Rahayu; Aulia Muhammad (Department of Public Administration, University Wijaykusuma Purwokerto, 2025)
The Smart Indonesia Program (PIP) aims to improve access and sustainability of education for underprivileged families, but still faces problems in the form of inaccurate targets, delays in disbursement, and mismatches in the amount of assistance with real educational needs. This study aims to evaluate the impact of PIP on improving access and sustainability of education. The research method uses a descriptive qualitative approach through evaluative literature review. The research population includes national and international journal articles, theses, dissertations, policy evaluation reports, and official government documents that discuss PIP or Smart Indonesia Card (KIP). Samples were selected using purposive sampling techniques based on criteria: discussing PIP/KIP, containing an impact analysis or evaluation of the program, published within the last ten years, and available in full text. Data was collected through a documentation study using a data extraction sheet, then analyzed by qualitative thematic analysis following the stages of data reduction, data presentation, and conclusion drawing according to Miles and Huberman. The results show that PIP is effective in increasing access to and participation in education, especially at the secondary and tertiary levels, as well as reducing the risk of dropping out, although its impact on the sustainability of secondary and long-term education is still limited. In conclusion, PIP makes a real contribution to improving access to education for underprivileged families, but it requires improvements in the aspects of target accuracy, distribution time, and amount of assistance.